2012
DOI: 10.1186/1743-422x-9-316
|View full text |Cite
|
Sign up to set email alerts
|

Human parainfluenza virus type 2 hemagglutinin-neuramindase gene: sequence and phylogenetic analysis of the Saudi strain Riyadh 105/2009

Abstract: BackgroundAlthough human parainfluenza type 2 (HPIV-2) virus is an important respiratory pathogen, a little is known about strains circulating in Saudi Arabia.FindingsAmong 180 nasopharyngeal aspirates collected from suspected cases in Riyadh, only one sample (0.56%) was confirmed HPIV-2 positive by nested RT-PCR. The sample that was designated Riyadh 105/2009 was used for sequencing and phylogenetic analysis of the most variable virus gene; the haemagglutinin-neuramindase (HN). Comparison of HN gene of Riyadh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
(10 reference statements)
3
12
0
Order By: Relevance
“…This study shows phylogenetic analysis of all coding regions of the HN gene and complete gene sequences of the F gene of HPIV2 submitted to the GenBank. Our results are in agreement with Terrier et al [] and Almajhdi et al [] and furthermore they show that both genes are equally suitable for this kind of analysis although longer sequences are advantageous when the analyzed strains are temporally and geographically highly related because of the low number of differences (isolate numbers 2995 and 3257 were identical in the HN gene sequence, but differed in three nucleotides in the F gene, and isolate numbers 16406 and 16971 were identical in the F gene but differed in one nucleotide in the HN gene). Only two isolate numbers 16967 and 17034 are found to have identical sequences in both genes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study shows phylogenetic analysis of all coding regions of the HN gene and complete gene sequences of the F gene of HPIV2 submitted to the GenBank. Our results are in agreement with Terrier et al [] and Almajhdi et al [] and furthermore they show that both genes are equally suitable for this kind of analysis although longer sequences are advantageous when the analyzed strains are temporally and geographically highly related because of the low number of differences (isolate numbers 2995 and 3257 were identical in the HN gene sequence, but differed in three nucleotides in the F gene, and isolate numbers 16406 and 16971 were identical in the F gene but differed in one nucleotide in the HN gene). Only two isolate numbers 16967 and 17034 are found to have identical sequences in both genes.…”
Section: Discussionsupporting
confidence: 93%
“…Previous phylogenetic studies [Terrier et al, ; Almajhdi et al, ] identified four clusters (G1–G4) with additional subclusters in clusters G1 and G4. These studies were based on the coding region of the HN gene.…”
Section: Discussionmentioning
confidence: 99%
“…We have added 38 new HPIV2 isolates ([8] and this study) and thus have generated adequate number of HPIV2 sequences to create a solid phylogenetic framework (Fig. 2) which confirms the distribution of HPIV2 isolates into four genotypes identified by [6]. Our previous study of genetic diversity of HPIV2 in Croatia between 2011 and 2014 betoken that the G1a genotype would take over the dominance of the G3 genotype in this period [8].…”
Section: Discussionsupporting
confidence: 69%
“…Phylogenetic analysis [7] identified two clusters within HPIV2 isolates but the low number of isolates gave poorly informative phylogenetic tree. Later, phylogenetic tree with more different worldwide HPIV2 isolates was constructed and suggested the existence of four clusters (G1–4) [6]. We have added 38 new HPIV2 isolates ([8] and this study) and thus have generated adequate number of HPIV2 sequences to create a solid phylogenetic framework (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation